2016
DOI: 10.1037/pro0000113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgment faith bias: Unexpected findings for psychology research and practice.

Abstract: Professional psychologists sometimes make more pathological judgments for clients with socially deviant faith (high religiousness or spirituality) than for otherwise identical clients with socially normative faith (low religiousness or spirituality). This phenomenon is called clinical judgment faith bias, and this study used mathematical modeling to investigate whether this occurs in psychological practice. Previously, Harris (2011) surveyed a national random sample of 141 psychologists in clinical practice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, some psychologists may hold unhelpful stereotypes about boys and men that undercut their effectiveness as psychotherapists (Mahalik et al, 2012). Other psychologists may have a clinical faith bias-a tendency to assign greater pathology to devoutly religious patients or religious patients with nonmainstream beliefs (Harris et al, 2016). Some will allow their personal like or dislike of patients to influence their clinical judgment.…”
Section: Humility or Healthy Self-doubtmentioning
confidence: 99%
“…For example, some psychologists may hold unhelpful stereotypes about boys and men that undercut their effectiveness as psychotherapists (Mahalik et al, 2012). Other psychologists may have a clinical faith bias-a tendency to assign greater pathology to devoutly religious patients or religious patients with nonmainstream beliefs (Harris et al, 2016). Some will allow their personal like or dislike of patients to influence their clinical judgment.…”
Section: Humility or Healthy Self-doubtmentioning
confidence: 99%
“…Compared with other helping professionals (e.g., clinical social workers, marriage and family therapists), psychologists' R/S beliefs and practices differ more from the general public: They are less likely to believe in God, more likely to claim no religious affiliation, and less likely to report that religion is important in their lives (Oxhandler et al, 2017). Furthermore, some studies have shown psychologists to exhibit biases toward religious patients (e.g., Ruff & Elliott, 2016); however, the sparse literature on this topic is mixed, with other studies finding no evidence of bias (e.g., Harris et al, 2016).…”
Section: Rationale For Collaborationmentioning
confidence: 99%